The dominant sink of oceanic calcium carbonate occurs in undersaturated seawater - Yiwei Wu; Yuefei Huang; Timothy DeVries; Hengdi Liang; Guangqian Wang; Shuo Zhang (Proceedings of the National Academy of Sciences, 2025)
Calcium carbonate (CaCO 3 ) particles formed by marine organisms dissolve in seawater and on the ocean floor, constituting a key component of the global ocean carbon cycle. However, neither the magnitude nor the distribution of CaCO 3 dissolution in the modern oceans is well constrained. Here we diagnose CaCO 3 dissolution rates in major oceanic regions and reconstruct CaCO 3 settling flux using a data-constrained ocean circulation model and observational climatologies of global seawater alkalinity and dissolved oxygen. Our approach distinguishes the effects of ocean circulation and CaCO 3 dissolution on seawater alkalinity and dissolved oxygen, and involves only one free parameter, a restoring timescale, which is constrained by compiling carbonate export rates estimated in the literature. We find that CaCO 3 dissolution in shallow waters (above the saturation horizon of aragonite) is much smaller than some recent estimates. Excluding the upper 114 m of the euphotic zone, the fraction of CaCO 3 dissolution within aragonite saturated waters is only about 16.5 ± 5.5%. About 39.8 ± 4.5% of CaCO 3 dissolution occurs below the aragonite saturation horizon but above the saturation horizon of calcite. The remaining 43.7 ± 3.8% dissolves in the deep ocean in undersaturated seawater. These results suggest that the seawater CaCO 3 saturation state is the primary control on CaCO 3 dissolution in the ocean.